Strategi Pengembangan Usaha Penjualan Daging Sapi Segar - Fery Mahendra; Maria Maria (Forum Agribisnis, 2023)
Berkah Sapi Business is a small business engaged in the sale or marketing of fresh beef. However, in running the business, Berkah Sapi experienced problems, especially in marketing beef. The selection and application of the right strategy in the development process will greatly affect the performance of the Blessing Cow Business. This study has the aim of knowing (1). determinants of success in developing the Berkah Sapi business in Pulutan Village, Sidorejo District, Salatiga City and (2) the strategy for developing the Berkah Sapi business. This research was conducted from January to March 2022. The respondents used were key informant (Mr. H. Muhammad Rofiq), informant 1 (mother Hjh. Sri Sundari) and informant 2 (Muhammad Aditya). From the results of this study, the main factor in the success of the Berkah Sapi Salatiga business is a strategic location, which is on the side of the road, has fresh quality meat and an affordable selling price (Rp. 120,000/kg. The development of the Berkah Sapi business uses the SO (Strength - Opportunities) strategy. ), which has a strategic location and fresh meat quality. With this strategy, Berkah Sapi must also pay attention to the sales promotion process to livestock care. The IFAS value is 0.72 and the EFAS is 0.16 which shows Berkah Sapi is in quadrant 1 progressive namely growing and developing. Blessings of Cows must continue to pay attention to the cleanliness of the cage to ensure the health and quality of beef so that consumer loyalty will increase and create additional market share. In addition, promotion through social media that leads to the importance of consuming quality beef will increase demand.